Dendrochronology of Quercus ilex L. and its potential use for climate reconstruction in the Mediterranean region - Campelo, F; Nabais, C; García-González, I; Cherubini, P; Gutiérrez, E; Freitas, H (Canadian Journal of Forest Research, 2009)
Holm oak (Quercus ilex L.) is a long-lived species widely distributed across the Mediterranean Basin, with potential value for dendrochronology and dendroclimatology. However, tree-ring dating in Q. ilex is a complex task that has limited the number of dendrochronological studies using this evergreen species. In the present work, it was investigated if old Q. ilex trees showed annual tree rings and whether they can be used as climate proxies. A long tree-ring chronology (126 years) of Q. ilex was developed using cross sections of 20 trees from the Guadiana river basin (Portugal). The high correlation among tree-ring series suggested that tree growth was controlled mainly by climate. Response function analysis showed a positive correlation between tree-ring width and precipitation from October(t–1) of the previous year to January(t) of the current year and in May(t). Tree-ring width was negatively correlated with the North Atlantic oscillation that exerts a strong influence on the precipitation over Iberia. Negative pointer years were triggered by dry years and became more frequent during the last decade of the 20th century. In conclusion, it is possible to accurately date old Q. ilex trees, and their tree rings could be used for climate reconstructions across the Mediterranean.
doi: 10.1139/X09-163
Keywords: climate reconstruction (PG); Dendrochronology; dendroclimatology; Quercus ilex

Relationships between climate and double rings in Quercus ilex from northeast Spain - Campelo, F; Gutiérrez, E; Ribas, M; Nabais, C; Freitas, H (Canadian Journal of Forest Research, 2007)
The influence of climatic factors on tree-ring width and the formation of double rings was studied in Quercus ilex L. growing in a coppice stand left unmanaged for 22 years. Ten trees were felled and discs were taken every 30 cm from bole and dominant branches. Dendrometer bands were installed on 10 nearby trees and the data recorded were used to confirm the accuracy of our tree-ring identification. They were also used to relate the seasonal radial growth pattern to double-ring formation. Double rings were frequent and occurred consistently along the stem. Two types of double rings could be recognized according to their width: type I, with the extra growth band accounting for approximately 50% of the tree ring; and type II, with a narrow extra growth band. Type I double rings were formed when approximately 1/2 of the growing-season precipitation occurred during the second growth period of the season and after the summer drought. Type II double rings occurred when approximately 1/3 of the precipitation in the growing season occurred after the summer drought. The formation of double rings was triggered by rainfall in summer and the extra growth-band width was related to summer and autumn environmental conditions. Double rings in Q. ilex can potentially be used in dendroclimatological studies, as they are formed in response to climatic conditions within the growing season.
doi: 10.1139/X07-050
Keywords: chronology (voyant); double rings; Drought; growth pattern; growth rings; Precipitation; Quercus ilex

Dendroanalysis: a tool for biomonitoring environmental pollution? - Nabais, C; Freitas, H; Hagemeyer, J (The Science of the total environment, 1999)
Trees of temperate regions usually form visible annual growth rings, which can be dated accurately. It is therefore possible to collect wood samples of different age and analyse their heavy metals content in order to get a chronological record of trace elements pollution in the tree's environment. This method of retrospective biomonitoring was called dendroanalysis. A basic assumption of dendroanalysis is the stability of the mineral distribution patterns, i.e. once the elements are stored, no significant mobility should occur. Additionally, neighbouring trees growing in the same environment should show similar radial element patterns. While some studies presented good correlations between radial distributions of heavy metals in tree rings and temporal records of pollution from industry or traffic, others failed in using dendroanalysis as a chronological record of pollution. Probably some elements can move at a certain rate in radial direction through the ray parenchyma cells. In this way the radial element distributions are subsequently changed. Growth rates of tree rings can also influence the concentrations of elements in wood. During periods of slow growth higher concentrations of elements can be found in the wood. Therefore, radial distribution patterns of heavy metals in tree rings should be used with caution as a tool for retrospective biomonitoring of environmental pollution.
Keywords: biomonitoring; Dendroanalysis; Heavy metals

Radial distribution of Ni in stemwood of Quercus ilex L. trees grown on serpentine and sandy loam (umbric leptosol) soils of NE-Portugal - Nabais, C; Freitas, H; Hagemeyer, J; Breckle, S W (Plant and soil, 1996)
Concentrations of Ni were determined in xylem and phloem of Quercus ilex trees growing on serpentine and sandy loam soils of northeast Portugal. Radial distribution patterns of Ni in stemwood were compared to variations in annual growth increments of the trees. Concentrations of Ni in xylem and phloem were higher in Q. ilex from serpentine soil, when compared with Q. ilex of a sandy loam soil. The radial distributions of Ni showed large variations among the trees, although they all grew in the same area within a short distance from each other. These differences can be caused by small-scale spatial variations in the soil. Therefore, the use of such radial Ni distributions for a retrospective biomonitoring of the Ni pollution of larger areas appears questionable.
Keywords: dendrochemistry; Nickel; Quercus ilex; serpentine; tree rings